Experiences of Special Education Teachers: How the Classroom Physical Environment Facilitates Socialization and Engagement of Students with Autism Spectrum Disorder? - Bhandari, Manoj; Shah, Umanga Jung Parakram (Journal of TESON, 2026)
This paper explores special education teachers’ experiences in engaging children in the physical environment where they work with students with autism spectrum disorder (ASD) to help them enhance social skills. We have used a qualitative phenomenological design to explore teachers’ experiences. We used purposive sampling to include two special education teachers who have been educating students with autism spectrum disorder from Kathmandu and Lalitpur districts as the sample. We collected information through face-to-face and phone interviews conducted repeatedly. We conducted thematic analysis by transcribing, coding, categorizing, and identifying themes. The importance of structured classroom environments and the tools and approaches, such as visual aids, sensory management, and skill development activities, is highlighted. Ethical concerns regarding restrictive seating practices for students with autism spectrum disorder are also raised. Therapy-combined activities like music, occupational, communication, and behavioral therapies to improve communication skills, social interaction, behavioral support, and motor skills were found to be efficient while teaching students with ASD. Daily co-teaching methods, individualized lesson plans, and continuous reinforcement promoting emotional support and a collaborative learning environment were identified as effective tools. The study emphasizes the significance of an inclusive, sensory-friendly, and well-structured physical classroom environment in establishing a supportive environment that helps students with autism spectrum disorder.